A REVIEW ON SIDDHA EXTERNAL THERAPY - NASIYAM (NASAL INSTILLATION) - B.K., Priya; S, Elansekaran; M, Ramamurthy; V, Srinivasan; M, Kanniyakumari; G.J, Christian (International Journal of Ayurveda and Pharma Research, 2018)
Siddha system of medicine, one of the ancient, traditional Indian systems of medicine has unique diagnostic methods, therapeutics and treatment procedures. It has a vast range of external modalities of treatment for health management. This external management is classified into 32 types. They include minor surgical procedures and treatment procedures. These therapies are used both as mainstream and supportive therapies - both curative and prophylactic. Most of the therapies are aimed to maintain the equilibrium of the three humours (Vatham, Pitham, Kabam). Among them Nasiyam (Nasal instillation) is one of the external therapies which is a non-invasive procedure. Nasiyam is the process by which the drug is administered through nostrils. This is the treatment procedure to balance the Thirithodam in its normal level. This paper documents the efficacy of Nasiyam, methods of application, shelf life, effect of Nasiyam in treating various diseases, the list of single drug and compound drug formulations that can be used as Nasiyam, Indications and contraindications are discussed in detail. Nasiyam therapy is used to treat the diseases of vitiated Kabam such as migraine, sinusitis, bronchial asthma, nasal polyp etc.